2011
DOI: 10.1186/1753-6561-5-s9-s83
|View full text |Cite
|
Sign up to set email alerts
|

Old lessons learned anew: family-based methods for detecting genes responsible for quantitative and qualitative traits in the Genetic Analysis Workshop 17 mini-exome sequence data

Abstract: Family-based study designs are again becoming popular as new next-generation sequencing technologies make whole-exome and whole-genome sequencing projects economically and temporally feasible. Here we evaluate the statistical properties of linkage analyses and family-based tests of association for the Genetic Analysis Workshop 17 mini-exome sequence data. Based on our results, the linkage methods using relative pairs or nuclear families had low power, with the best results coming from variance components linka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 8 publications
0
16
0
Order By: Relevance
“…Simpson et al [2011] found that the nuclear family-based tests of association (ROMP and ASSOC) were more powerful than the linkage methods in detecting variants with causal effects on the quantitative traits Q1 and Q2 but that they also lacked stringent control of type I error.…”
Section: Resultsmentioning
confidence: 99%
“…Simpson et al [2011] found that the nuclear family-based tests of association (ROMP and ASSOC) were more powerful than the linkage methods in detecting variants with causal effects on the quantitative traits Q1 and Q2 but that they also lacked stringent control of type I error.…”
Section: Resultsmentioning
confidence: 99%
“…37 Thus, these linkage results may be very useful in WGS studies of individuals with a family history of PrCa, because they will allow us to prioritize these regions in the search for rare variants with major effects on PrCa risk. [81][82][83] …”
Section: Discussionmentioning
confidence: 99%
“…The strategy has also been both proposed and used in the search for loci contributing to complex traits (Wright et al 1999). This same strategy of using large pedigrees also worked well to identify loci for simulated trait data as part of Genetic Analysis Workshop 17 (Gagnon et al 2011; Simpson et al 2011; Wilson and Ziegler 2011) in which evidence for linkage was clearly identified in the large pedigrees, without a clear comparable signal in sequence data available for unrelated subjects.…”
Section: Advantages Of Family-based Designsmentioning
confidence: 94%
“…The trait loci may represent single genes with relatively high effects, or several closely linked loci, each with moderate effects that together have a large effect (Yazbek et al 2011). Large pedigrees intrinsically have more power for detection of linkage or estimation of effects than do equivalent-sized samples of smaller families (Wijsman and Amos 1997) or unrelated subjects, particularly in the presence of rare variants such as those found in sequence data (Gagnon et al 2011; Simpson et al 2011; Wilson and Ziegler 2011). If pedigrees are sufficiently large, they can individually implicate genomic regions.…”
Section: Advantages Of Family-based Designsmentioning
confidence: 99%